A Main Sequence for Quasars - Marziani, Paola; Dultzin, Deborah; Sulentic, Jack W.; Del Olmo, Ascensión; Negrete, C. A.; Martínez-Aldama, Mary L.; D'Onofrio, Mauro; Bon, Edi; Bon, Natasa; Stirpe, Giovanna M. (Frontiers in Astronomy and Space Sciences, 2018)
The last 25 years saw a major step forward in the analysis of optical and UV spectroscopic data of large quasar samples. Multivariate statistical approaches have led to the definition of systematic trends in observational properties that are the basis of physical and dynamical modeling of quasar structure. We discuss the empirical correlates of the so-called “main sequence” associated with the quasar Eigenvector 1, its governing physical parameters and several implications on our view of the quasar structure, as well as some luminosity effects associated with the virialized component of the line emitting regions. We also briefly discuss quasars in a segment of the main sequence that includes the strongest FeII emitters. These sources show a small dispersion around a well-defined Eddington ratio value, a property which makes them potential Eddington standard candles.